Analysis of the Implementation of a Classroom Reading Corner in Improving Fifth-Grade Students’ Reading Interest in Basic Education: A Study at SDN 116 Percontohan - Yenni Efrida Lubis; Rahmi Seri Hanida; Resdilla Pratiwi (cendekia citra gemilang, 2026)
Reading interest is a foundational element of literacy success among elementary school students, yet its cultivation in classrooms is often constrained by limited access to reading materials. This study analyzes the implementation of a classroom reading corner (pojok baca) in fostering fifth-grade students’ reading interest at SDN 116 Percontohan and identifies its supporting and inhibiting factors. A descriptive qualitative approach was employed, involving 21 fifth-grade students (14 boys, 7 girls), a homeroom teacher, and a school principal as informants selected through purposive sampling. Data were collected through non-participant observation, semi-structured interviews, and documentation, validated through method triangulation, and analyzed using the Miles and Huberman interactive model. The results show that the implementation of the reading corner took place through six interrelated aspects: provision of the reading corner, availability of facilities and book collections, implementation of the literacy program, utilization in the learning process, teacher motivation, and independent use by students. Supporting factors included principal support, active teacher involvement, adequate facilities, student enthusiasm, and ease of access, while limited book collections and suboptimal supervision were the main obstacles. These findings extend prior research by showing that the success of reading corners depends more on institutional synergy than on the availability of physical facilities alone. The findings imply that, at the basic-education level, cultivating reading interest requires schools and teachers to treat the reading corner not as a facility to be provided once but as a pedagogical practice to be actively managed: for teachers, this means embedding guided reading routines into daily instruction, and for schools, aligning budgeting and supervision policies so that collections stay fresh and the corner is consistently used. Accordingly, this study recommends strengthening book-procurement budgets and establishing a rotating literacy-duty supervision system, and it invites future research to examine how such institutional synergy shapes students’ long-term reading behaviour.